From Support to Mutiny: Shifting Legitimacy Judgments and Emotional Reactions Impacting the Implementation of Radical Change - Huy, Quy Nguyen; Corley, Kevin G.; Kraatz, Matthew S. (Academy of Management Journal, 2014)
Based on a three-year inductive study of one organization's implementation of radical organizational change, we examine the critical role played by middle managers' judgments of the legitimacy of their top managers as change agents. Our analysis revealed middle managers' shifting judgments of the change agents' legitimacy that arose with their emotional reactions and produced rising resistance to the change effort. Our inductive model illustrates the dynamic, relational, and iterative relationships among change recipients' legitimacy judgments of change agents and arising emotional reactions in various phases of planned change, which explain recipients' emergent resistance to the change effort. Our model allows us to contribute to theory on radical organizational change, resistance to change, and legitimacy judgments.